2020
DOI: 10.3389/fphar.2020.01334
|View full text |Cite
|
Sign up to set email alerts
|

“Don’t Let Medicines Go to Waste”—A Survey-Based Cross-Sectional Study of Pharmacists’ Waste-Reducing Activities Across Gulf Cooperation Council Countries

Abstract: Objectives Medication waste has a negative environmental and economic impact. From avoiding unnecessary supply to recycling medicines that are no longer needed, pharmacists are placed in an advantageous position to minimise medication waste. Thus, the aim of this study was to detect waste-minimising activities undertaken by pharmacists to limit medication waste and to evaluate their importance for medication waste minimisation and feasibility for implementation. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Expired medications are usually collected at a centralized company facility, which then is managed and incinerated by external waste management companies. There are other methods of reducing medicine wastage such as exchanging stocks with other pharmacies, medication reconciliation with customers and adjusting the quantities during dispensing, especially during the treatment initiation stage where patients are more likely to discontinue their treatment ( 21 24 ). Re-dispensing of returned medications is not practiced in Malaysia because of concerns regarding risks to patients arising from the condition of returned medications and the presence of counterfeit products ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Expired medications are usually collected at a centralized company facility, which then is managed and incinerated by external waste management companies. There are other methods of reducing medicine wastage such as exchanging stocks with other pharmacies, medication reconciliation with customers and adjusting the quantities during dispensing, especially during the treatment initiation stage where patients are more likely to discontinue their treatment ( 21 24 ). Re-dispensing of returned medications is not practiced in Malaysia because of concerns regarding risks to patients arising from the condition of returned medications and the presence of counterfeit products ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Faten Alhomoud conducted a survey to study the waste-reducing activities among the practicing pharmacists in the Gulf region countries. Pharmacists participating in this study believe in the importance of reducing drug-waste; however, waste-reducing activities were not practiced continuously [ 16 ]. A study found that on average, 2–3 drugs are expired per household in Saudi [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medication wastage is a global issue. [7][8][9][10][11][12][13][14][15][16] The definition of medication wastage was given in a report that used the Delphi technique as follows: "Medication wastage refers to any medication which expires or remains unused throughout the whole medicines supply chain. Also refers to the unnecessary or inappropriate consumption of medications by patients, or the unjustified non-adherence to treatment guidelines by healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%